The sociology of children, childhood and generation - Leonard, Madeleine (SAGE, 2016)
"This book illustrates sociology's distinctive contribution to childhood studies and to understanding contemporary children and childhood. By focusing specifically on the ongoing thorny relationship between structure and agency, the book highlights the messy and interrelated ways in which children's everyday micro lives are influenced by wider macro structures." -- Provided by publisher